PERBEDAAN USAHATANI KANGKUNG DARAT (Ipomoea aquatica) SISTEM ORGANIK DAN ANORGANIK - Supriyono, Edi; Ardisela, Dawud; Rani, Ismarani (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
Different farming Ipomoea aquatica system of organic and inorganicin Agro Cilangkap Garden of Jakarta. This research uses experimental methods that the application of inorganic and organic system susing pairedplots. In the applied organic farming plots with technology and control of plant pests.The results showed Ipomoea aquatica farming land with organic systemis more favorableto the 88.89% difference with in organic systems. Break Even Point (BEP) and theamountof productionvalue to the organic and inorganic system sisabove thevalue of BEP.